Introduction to Intellectual Property - Kline, David; Kappos, David (Open textbook library., 2021)
Introduction to Intellectual Property provides a clear, effective introduction to patents, copyright, trademarks, and trade secrets. The text may be used by students and instructors in formal courses, as well as those applying intellectual property considerations to entrepreneurship, marketing, law, computer science, engineering, design, or other fields. The luminaries involved with this project represent the forefront of knowledge and experience, and the material offers considerable examples and scenarios, as well as exercises and references. Introduction to Intellectual Property was originally developed by the Michelson 20MM Foundation, released under the title The Intangible Advantage.